Encapsulation of Chokeberry Polyphenols by Ionic Gelation: Impact of Pullulan and Disaccharides Addition to Alginate Beads - Mirela Kopjar; Ina Ćorković; Josip Šimunović; Anita Pichler (Applied Sciences)
Alginate is one of the most utilized biopolymers for the encapsulation of polyphenols throughout ionic gelation. For improvement in the encapsulation of polyphenols, other biopolymers and/or fillers can be employed. The purpose of this study was to include pullulan and/or disaccharides in an alginate encapsulation mixture to monitor whether we would achieve higher encapsulation of chokeberry juice polyphenols. Alginate hydrogel beads were used as controls, and through the results for total polyphenol and proanthocyanidin contents, concentrations of individual polyphenols, and antioxidant activities, it can be observed that pullulan and/or disaccharides had an impact on the encapsulation of these bioactives. Alginate/pullulan hydrogel beads had the highest contents of total polyphenols and proanthocyanidins (8.60 g/kg and 2.37 g/kg, respectively), whereas alginate/trehalose hydrogel beads had the lowest (5.50 g/kg and 1.16 g/kg, respectively). All hydrogel beads, except alginate/pullulan/sucrose, had higher anthocyanin (cyanidin-3-galactoside and cyanidin-3-arabinoside) contents than alginate beads (404.37 mg/kg and 89.97 mg/kg, respectively), but the most efficient combination for encapsulation of chokeberry anthocyanins was alginate/pullulan (477.32 mg/kg and 109.60 mg/kg, respectively). The highest concentration of neochlorogenic acid was determined in controls (260.14 mg/kg), while the highest concentration of chlorogenic acid in alginate/pullulan/sucrose beads (229.51 mg/kg). Quercetin-3-glucoside was evaluated as having the highest concentration in alginate/pullulan hydrogel beads (35.45 mg/kg). The data obtained through this study highlight the importance of the composition of an encapsulation mixture in order to achieve high encapsulation of chokeberry juice polyphenols. High encapsulation efficiency was obtained for anthocyanins, especially when pullulan was used in combination with alginate.